Navigating the Business Landscape: The Influence of Infrastructure, Financial Inclusion, Innovation, and Government Policy on Indonesian MSMEs - Fahrati, Eny; Kusno, Hendra Sanjaya; Safitri, Elvina (International Journal of Business, Law, and Education, 2024)
The performance of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia is examined in this study in relation to a number of different influences. A quantitative examination of 255 MSMEs from various industries, geographies, and sizes is carried out, with an emphasis on the interplay of infrastructure, financial inclusion, innovation, and government policy. In order to investigate the direct and intermediary links between these important determinants and MSME performance, structural equation modeling was employed in the study. The results revealed a strong positive correlation between the variables, demonstrating the critical role that government policies, infrastructure, financial inclusion, and innovation play in fostering business success. Financial inclusion plays a mediating role, and mediation analysis clarifies the contextual elements influencing the connections that are seen. By providing practical insights for business leaders and policymakers to navigate and enhance the business environment, this research advances our understanding of the intricate dynamics inside Indonesia's MSME sector